Eksplorasi Translasi Representasi Matematis Mahasiswa dalam Penyelesaian Masalah Analisis Validitas Argumen - Hadi, Mei Rina (Jurnal Tadris Matematika, 2024)
The ability to translate among mathematical representations is one of the 21st-century skills that students need to have. This ability is often challenging for students, especially in translating verbal to symbolic or visual forms. One of the materials that requires translation skills is argument validity analysis. This study aims to explore the mathematical translation process of students use in completing argument validity analysis. This study is a qualitative study with an exploratory approach. The subjects of the study were 3 Mathematics Education students who were selected through purposive sampling and analyzed in depth using Polya's problem-solving stages and Bosse's translation process. The results showed that the problem-solving process went hand in hand with mathematical translation activities. Subjects who carried out the mathematical translation process correctly and completely tended to solve problems better. Subjects made several mistakes in the translation process, including misinterpretation and implementation errors that resulted in inaccurate argument validity analysis. These findings indicate that mathematical translation skills are an important basis for solving argument validity analysis problems. Therefore, learning strategies that support the improvement of mathematical translation skills need to be developed to strengthen students' critical thinking skills in analyzing the validity of arguments at the higher education level.